Menjadi Saksi Kristus di Era Moderasi Beragama: Aktualisasi Amanat Agung dalam Kehidupan Orang Percaya - Hisar Parulyan; Ayub Sugiharto (Sekolah Tinggi Teologi Berita Hidup, 2026)
This study discusses the role of believers in actualizing the Great Commission amid religious moderation, with a focus on the call to be witnesses of Christ in a pluralistic modern era. In the context of a diverse society, witnessing one's faith is not only manifested through verbal evangelism, but also through concrete actions that reflect the love, truth, and peace of Christ. Through a qualitative descriptive approach and literature study, this research explores how believers can carry out the Great Commission wisely, relevantly, and contextually amid the trend of religious moderation that demands tolerance and respect for differences. The results of the study show that being a witness of Christ means living as a representation of God's love in words, deeds, and attitudes toward others. True witness of faith is not coercive, but presents goodness that can be felt by all people. In an era of religious moderation, believers are called to act as peacemakers, engage in interfaith dialogue, and reject all forms of violence and hate speech. Consistent and loving witness is an effective means of introducing Christ without causing conflict between religious communities. Practically speaking, this study confirms that the actualization of the Great Commission today must be realized through exemplary lives, both in social environments and in the digital world. The church and Christians need to strengthen faith education, build Christ-like character in the congregation, and develop creative witnessing strategies that are relevant to the context of a pluralistic society. In this way, believers can live as the light and salt of the world, bringing Christ's love to life, so that the Great Commission continues to be realized in a peaceful, just, and loving community.